Plant-growth-promoting bacteria from rhizosphere of Chilean common bean ecotype (Phaseolus vulgaris L.) supporting seed germination and growth against salinity stress - Meza, Cynthia; Valenzuela, Francisca; Echeverría-Vega, Alex; Gomez, Aleydis; Sarkar, Shrabana; Cabeza, Ricardo A.; Arencibia, Ariel D.; Quiroz, Karla; Carrasco, Basilio; Banerjee, Aparna (Frontiers in Plant Science, 2022)
Salinity abiotic stress is increasing day by day due to continuous global warming as well as climate change. This is also becoming one of the major causes behind the reduction in crop production. Plant-bacteria interaction plays an essential role in improving crop yield without using any chemical fertilizers. The present study aims to characterize the interaction between plant growth-promoting bacteria (PGPB) and their role in mitigating salinity stress for local variety crops. Therefore, in this work, two PGPB Bacillus proteolyticus Cyn1 and Bacillus safensis Cyn2 were isolated from rhizospheric soil of the Chilean common bean ecotype ՙSapito՚ (Phaseolus vulgaris L.) and their PGPB traits were analyzed. Cyn1 can produce NH3, HCN, and also secrete siderophores, whereas Cyn2 produce NH3 and siderophores but responded negatively to HCN production. Both the isolated bacteria have shown a positive result for ACC deaminase production, phosphate solubilization, and catalase enzyme secretion. Under all three tested abiotic stresses, i.e. temperature, water, and salinity, both the bacteria as well as their consortium have demonstrated positive responses. . Cyn 1 under salinity stress as well as water stress can produce biofilm network to combat the stress. While under salinity stress, both the PGPB isolates indicated the production of stress components and cytoplasmic inclusion bodies. Based on the response, among all other abiotic stresses, salinity stress, was chosen for further plant-bacteria interaction study and growth. Visible root colonization of the bacteria have been observed in comparison to the control. The germination index was 100% for all experimental setups of seed bacterization, both under control conditions and salinity stress. Both bacteria responded with good PGP traits that helped in the growth of healthy plants after the bacterial treatment in final pot experiments. Additionally, the consortium and the plants treated with Cyn1 have demonstrated high production of photosynthetic pigments in both experimental setups. As both B. proteolyticus Cyn1 and B. safensis Cyn2 have shown promising PGPB characters as well as efficient response against toxicity related to salinity., Hence, both of these bacteria as well as consortium can be used for improved agricultural production of Chilean native common beans in near future.